Morphological peculiarities of pulmonary hamartoma: two cases of cardiosurgical patients - V. P. Zakharova; O. V. Rudenko; S. I. Dorofeeva (Ukrainian Journal of Cardiovascular Surgery, 2017)
The article presents two observations of pulmonary hamartoma in patients, which were operated on the cardiosurgical pathology and neoplasm of the lung.Purpose of the work: to study the morphological features of the pulmonary hamartoma. The tumors study was performed by macroscopic description of the surgical material and microscopic analysis of histological preparations stained with hematoxylin and eosin, by van Gison, fukselin by Weigert, Sudan III-IV and MSB method. The morphological features of these tumors have been determined, that allowed to identify neoplasms as hamartomas, the predominant component of which structure was cartilage tissue. In addition, they contained elements of fat and fibrous tissue, as well as bronchial epithelium. In one case the tumor was removed with adjacent pulmonary tissue and its changes were evaluated as a result of compression of the lung by pulmonary hamartoma.